Motivasi Tenaga Pendidik dalam Mengatasi Kesulitan Belajar Anak Berkebutuhan Khusus (International Forum of Researchers and Lecturers, 2023)
Apart from being a teacher, the teacher also plays an important role as a motivator (motivator or generates motivation for students). In almost every school we will encounter cases of children who are unable to achieve achievements. The achievements referred to in this case do not always have to be in terms of being class champions, but can be defined in other words, children are able to follow the lessons given by the teacher during the learning process. Children with special needs or what we often know as ABK are children who really need help in the form of special treatment from educators who have more experience and understanding of children with special needs.ABK is also the same as other normal humans who need proper educational services. Where through these educational services it is hoped that those with special needs have an environment to be able to establish interactions with other friends, besides that they are also expected to be able to develop the abilities and potential that exist within them. As for the types of children with special needs, they include: 1) cleft (speech impaired) 2) blind (blind) 3) hearing (deaf) 4) paralyzed (damaged) 5) emotional disorders (handicapped) 6) down syndrome 7) Children with Learning Difficulties.